Non-persistence with multiple secondary prevention medications for peripheral arterial disease among older hypertensive patients - Wawruch, Martin; Petrova, Miriam; Celovska, Denisa; Alfian, Sofa D.; Tesar, Tomas; Murin, Jan; Trnka, Michal; Paduch, Tomas; Aarnio, Emma (Frontiers in Pharmacology, 2024)
The benefit of secondary prevention in hypertensive patients with peripheral arterial disease (PAD) is based on continual simultaneous taking of statins, antiplatelet agents and antihypertensive agents, preferably angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs). Our study was aimed at a) the analysis of the extent of non-persistence with multiple medication classes, and b) identifying factors associated with the likelihood of nonpersistence.In our cohort study, 3401 hypertensive patients (1853 females and 1548 males) aged ≥65 years treated simultaneously with statins, antiplatelet agents and ACEIs/ARBs and in whom PAD was newly diagnosed during 2012 were analysed. A patient was classified as non-persistent when he/she was non-persistent with at least one of the three analysed medication classes. The most important characteristics associated with the probability of non-persistence were identified using the Cox regression.Results: At the end of the follow-up period (mean length 1.8 years), 1869 (55.0%) patients (including 1090 females and 779 males) were classified as non-persistent. In the whole study cohort, factors associated with non-persistence were female sex, atrial fibrillation, and being a new user of at least one of the analysed medication classes; in males, they were university education, atrial fibrillation, and epilepsy, and, in females, being a new user.Identification of sex differences in factors associated with non-persistence makes it possible to determine the groups of patients in whom special attention should be paid to improving their persistence with a combination of medicines in order to ensure successful secondary prevention of PAD.